RESEARCH OF THE VALIDITY BOUNDARIES OF INTEGRATION TESTS IN A LOCALLY REPRODUCED CLOUD EXECUTION ENVIRONMENT - Суприган, Віталій; Лебідь, Олександр (SWorldJournal, 2026)
In modern cloud-native systems, software testing increasingly depends on the characteristics of the execution environment in which integration checks are performed. Unlike traditional quality assurance approaches, where the test environment is often cons